The Role of Zakat, Infaq and Shadaqah (ZIS) in Reducing Poverty in Aceh Province - Saputro, Eko Gondo; Sidiq, Sahabudin (Universitas Muhammadiyah Yogyakarta, 2020)
Aceh is one of the provinces that paves the way for the Islamic development in Indonesia. Therefore, Aceh has a strong Islam preaching and becomes the center of science. Innovations made in Islamic knowledge with government policies in managing zakat funds collected from the community-made Aceh are through the BAZNAS in provincial level namely Baitul Mal Aceh; one of the BAZNAS with highly effective Allocation to Collection Ratio (ACR) levels. Baitul Mal Aceh has a superior program aiming at making Mustahik into Muzzaki consisting of education, health assistance, and economic empowerment programs. This research was conducted to see the effect of Zakat, Infaq, Shadaqah (ZIS) through Economic Growth, Education, Health, and HDI on Poverty in Aceh. The method used in this research was Structural Equation Model-Partial Least Square (SEM-PLS). The results revealed the direct effect of ZIS on Economic Growth, Health, and HDI, as well as the total indirect effect of ZIS on Economic Growth and Poverty in Aceh. The results also showed that the effect of ZIS through Health and HDI on Economic Growth and the effect of ZIS through HDI on Poverty in Aceh.